Surface and diving metabolic rates, and dynamic aerobic dive limits ( dADL ) in near‐ and off‐shore bottlenose dolphins, Tursiops spp., indicate that deep diving is energetically cheap - Andreas Fahlman; Austin S. Allen; Ashley Blawas; Jay Sweeney; Rae Stone; Robyn Faulkner Trainor; Frants H. Jensen; Katherine McHugh; Jason B. Allen; Aaron A. Barleycorn; Randall S. Wells (Marine Mammal Science, 2023)
High‐resolution dive depth and acceleration recordings from nearshore (Sarasota Bay, dive depth Tursiops spp.) were used to estimate the diving metabolic rate (DMR) and the locomotor metabolic rate (LMR, L O 2 /min) during three phases of diving (descent, bottom, and ascent). For shallow dives (depth ≤ 30 m), we found no differences between the two ecotypes in the LMR during diving, nor during the postdive shallow interval between dives. For intermediate (30 m 100 m), the LMR was significantly higher during ascent than during descent and the bottom phase by 59% and 9%, respectively. In addition, the rate of change in depth during descent and ascent (meters/second) increased with maximal dive depth. The dynamic aerobic dive limit (dADL) was calculated from the estimated DMR and the estimated predive O 2 stores. For the Bermuda dolphins, the dADL decreased with dive depth, and was 18.7, 15.4, and 11.1 min for shallow, intermediate, and deep dives, respectively. These results provide a useful approach to understand the complex nature of physiological interactions between aerobic metabolism, energy use, and diving capacity.